Smart Mobility Development Through Public Transportation in the Special Region of Yogyakarta - PTP, Raden Rara Dyah Pinasthika; Atmojo, Muhammad Eko (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2026)
This research was conducted to determine the readiness of the Special Region of Yogyakarta (DIY) Government in realizing smart mobility through Trans Jogja public transportation services. Amidst the challenges of urbanization and the increasing need for efficient mobility, this research examines the implementation of the smart mobility concept in the context of Trans Jogja as a Bus Rapid Transit (BRT) system. The research method used is descriptive qualitative, with data collection through semi-structured interviews with representatives of the DIY Transportation Agency, PT AMI, and Trans Jogja users. The results showed that the DIY Government has made efforts to develop Trans Jogja services based on smart mobility, including fleet and route upgrades, as well as the utilization of the Trans Jogja application. However, the provision of more efficient and equitable routes, the addition of bus stops, and maximizing service convenience still need more attention.